Acoustic emission in moistened bricks and wood - KOŁTOŃSKI, W. (Archives of Acoustics, 1995)
Initial investigations were carried out concerning an occurrence of acoustic emission in different kinds of bricks and woods under moistening. The results are presented and discussed of these investigations and possibilities of their practical applications for finding out water leakages in places difficult of access in buildings made of bricks and wood.